Key Influencers in Public Diplomacy 2.0: A Country-Based Social Network Analysis. (January 2021) - Ingenhoff, Diana; Calamai, Giada; Sevin, Efe
This article presents a study of Twitter-based communication in order to identify key influencers and to assess the role of their communication in shaping country images. The analysis is based on a 2-month dataset comprised of all tweets including hashtags of the three countries selected for this study: Austria, Switzerland, and the Netherlands. Following a two-step flow model of communication, we initially identified the influential Twitter users in all three countries based on their centrality measures. Subsequently, we carried out a qualitative content analysis of tweets posted by these influential users. Finally, we assessed the similarities and differences across the three country cases. This article offers new insights into public diplomacy 2.0 activities by discussing influence within the context of country images and demonstrating how opinion leaders can play a more dominant role than states or other political actors in creating and disseminating content related to country image. The findings also provide practical insights in the production of a country's image and its representation on new media platforms.